2010
DOI: 10.1007/s10562-010-0339-7
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Gold-Catalyzed Reactions of Diazoalkanes with Amines and O2 to Give Enamines

Abstract: Bulk gold powder, consisting of approximately 5-50 lm particles, catalyzes reactions of diazoalkanes E(H)C=N 2 , where E is CO 2 Et or PhC(O), with amines R 1 R 2 NH and O 2 to give enamine products (R 1 R 2 N) (E)C=CH(E) in 58-94% yield. The reactions are proposed to occur by initial formation of surface-bound (E)(H)C: carbene groups that are attacked by nucleophilic amines. The enamine products are very different than those obtained in reactions catalyzed by homogeneous transition metal complexes. These reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…155 This reaction, which occurs in high yields (58-94%), is interesting because no report of other catalytic system is known and the process is quite simple to apply.…”
Section: Oxidation Of Aminesmentioning
confidence: 99%
“…155 This reaction, which occurs in high yields (58-94%), is interesting because no report of other catalytic system is known and the process is quite simple to apply.…”
Section: Oxidation Of Aminesmentioning
confidence: 99%
“…However, our group has recently found that bulk gold also catalyzes several oxidations in which O 2 is the oxidant. These include the reaction of isocyanides with amines to produce carbodiimides [8] or ureas [9], reactions of carbon monoxide with primary amines to afford ureas [10], and reactions of diazoalkanes with amines to give enamines [11]. In addition, bulk gold catalyzes the oxidative dehydrogenation of amines to imines using O 2 as the oxidant (Eqs.1-3) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The engineering of designer surfaces functionalized with carbenes [50,51,[216][217][218], and the redox properties and intervalence charge transfer of such organometallic systems on electrode surfaces [219] are other rapidly expanding focus areas. A class of multimetal multicarbene complexes with great potential includes those with a large number of carbene ligands found in close proximity to each other in macromolecular assemblies or surfaces.…”
Section: Discussionmentioning
confidence: 99%